Board and card games project to raise awareness of school bullying - Araujo, Fabrício Coutinho de; Teixeira, Fernando de Souza; Santos, Julio Nico Dantas do; Barbosa, Ramon de Souza; Silva, Sandra Regina Rocha (Seven Editora, 2023)
Systematic bullying is any act of physical or psychological, intentional and repetitive violence that occurs without evident motivation, practiced by an individual or group, against one or more people, to intimidate or assault them, causing pain and anguish to the victim, in a relationship of the power imbalance between the parties involved. The objective of this work is to an experience in teaching propose school games to raise awareness of school bullying. The games were designed in a multidisciplinary manner by undergraduate students who had no prior experience in building games. The theme of bullying was exposed in two projects funded by FAPES. Two games were designed: a board game and a card game. The design of the games was based on two methodologies from the area of Human Machine Interface, the user-centered design and the usability test. The pilot usability test was applied to the prototypes of the games created, which raised improvements that were later implemented in the projects. The students have also prepared all the necessary documentation for the ethics committee so that the game can be later refined in the last phase using a usability test with the children of a school. DOI:https://doi.org/10.56238/devopinterscie-228